Space-borne Bose–Einstein condensation for precision interferometry. (18th October 2018) - Becker, Dennis; Lachmann, Maike; Seidel, Stephan; Ahlers, Holger; Dinkelaker, Aline; Grosse, Jens; Hellmig, Ortwin; Müntinga, Hauke; Schkolnik, Vladimir; Wendrich, Thijs; Wenzlawski, André; Weps, Benjamin; et al.
Abstract Owing to the low-gravity conditions in space, space-borne laboratories enable experiments with extended free-fall times. Because Bose–Einstein condensates have an extremely low expansion energy, space-borne atom interferometers based on Bose–Einstein condensation have the potential to have much greater sensitivity to inertial forces than do similar ground-based interferometers. On 23 January 2017, as part of the sounding-rocket mission MAIUS-1, we created Bose–Einstein condensates in space and conducted 110 experiments central to matter-wave interferometry, including laser cooling and trapping of atoms in the presence of the large accelerations experienced during launch. Here we report on experiments conducted during the six minutes of in-space flight in which we studied the phase transition from a thermal ensemble to a Bose–Einstein condensate and the collective dynamics of the resulting condensate. Our results provide insights into conducting cold-atom experiments in space, such as precision interferometry, and pave the way to miniaturizing cold-atom and photon-based quantum information concepts for satellite-based implementation. In addition, space-borne Bose–Einstein condensation opens up the possibility of quantum gas experiments in low-gravity conditions1, 2 . A Bose–Einstein condensate is created in space that has sufficient stability to enable its characteristic dynamics to be studied.